ДЕВИАНТ ХУЛҚЛИ ЎСМИРЛАРНИ ТАРБИЯЛАШДА НИМАЛАРГА ЭЪТИБОР БЕРИШ КЕРАК? (Conferencea, 2022)
This article discusses what to look for when raising teens with deviant behavior. Self-awareness is important for the development of adolescents. This is because in the process of selfrealization, the desire and desire to evaluate oneself, to compare oneself with other people, and the need to build oneself arose